Polish plants as raw materials for cosmetic purposes - Mietlińska, Katarzyna; Przybyt, Małgorzata; Kalemba, Danuta (Wydawnictwo Politechniki Łódzkiej, 2019)
The cosmetics market is more and more demanding, and there is a constant request for new products. The aim of the study was to find plant materials occurring commonly in Poland that would have a multidirectional effect on the skin. Research focuses on plants with high content of saponins and polyphenols. Ability to create foam and ability to reduce the surface tension of water as a determinant of saponin content was checked. The Folin-Ciocalteu test was made to check the content of polyphenols. Fifty-seven raw materials were examined. To the most promising for cosmetic purposes belong goldenrods (Solidago), especially their leaves. Much better resu lts were obtained for S. canadensis and S. gigantea, than S. virgaurea.
Keywords: saponins; polyphenols; cosmetics; herbs; screening; saponiny; polifenole; kosmetyki; zioła